Gel-cast hierarchical porous B4C/C preform and its role in fabricating reaction bonded boron carbide composites. Issue 5 (1st April 2017) - Xu, Yufeng; Ru, Hongqiang; Long, Haibo; Zhao, Jing; Wang, Wei; Yue, Xinyan
Abstract: The resorcinol-formaldehyde (RF) gel-casting system is employed for the first time to fabricate a hierarchical porous B4 C/C preform, which was subsequently used for the fabrication of reaction bonded boron carbide (RBBC) composites via a liquid silicon infiltration process. The effect of the carbon content and carbon structures of this perform on the microstructures and mechanical properties of B4 C/C preform and the resultant RBBC composites is reported. The B4 C/C preform (16 wt% carbon) exhibit a strength of 34±1 MPa. The obtained RBBC composites shown uniform microstructure is consisted of SiC particles bonded boron carbide scaffold and an interpenetrating residual silicon phase. The Vickers hardness, flexural strength and fracture toughness of the RBBC composites (16 wt% carbon) are 24 GPa, 452 MPa and 4.32 MPa m 1/2, respectively.